Minimum energy control of fractional-order differential-algebraic system - Muhafzan; Zulakmal; Yulanda Mardiana Putri; Leong, Wah June (Russian Academy of Sciences, Institute of Problems in Mechanical Engineering, 2022)
This paper discusses the minimum energy control problem of fractional-order differential-algebraic system. The main aim of this paper is to find the minimum energy that drives an initial state of the fractional order differential-algebraic system to the zero state such that an index performance is minimized. The method of solving is to convert the minimum energy control problem of fractional-order differential-algebraic system into the standard fractional-order linear quadratic optimization problem by using a transformation and further solve the standard fractional-order linear quadratic optimization using the available theory in the literature. Under some particular conditions, we find the explicit formulas of the minimum energy control of fractional-order differential-algebraic system in Mittag-Leffler terms.